Comparison of user experience in online programming learning platforms: Case study in novice programmers from Huancayo, Peru - Taipe Miranda, Gino Joel (2021)
This research was comparison of user experience between the Scratch and Code.org platforms, for being used by novice program-mers. The comparison was taking into seven factors that influ-ence user experience, including usefulness, usability, desirability, findability, accessibility, credibility, and value. The research was carried out with the participation of 40 people with little or no knowledge about programming topics, the people carried out the following tasks: Register on the platform, use a sample project, create a project, program using block-based programming, explore the features and functionalities of the platform. In general, both platforms offer a good user experience for novice programmers. Finally, it is concluded that Scratch offers a better user experience, because it exceeded Code.org in 4 of the 7 factors.